A Study on Propagation Models for 60 GHz Signals in Indoor Environments - Carneiro de Souza, Letícia; de Souza Lopes, Celso Henrique; de Cassia Carlleti dos Santos, Rita; Cerqueira Sodré Junior, Arismar; Mendes, Luciano Leonel (Frontiers in Communications and Networks, 2022)
The millimeter-waves band will enable multi-gigabit data transmissions due to the large available bandwidth and it is a promising solution for the spectrum scarcity below 6 GHz in future generations of mobile networks. In particular, the 60 GHz band will play a crucial role in providing high-capacity data links for indoor applications. In this context, this tutorial presents a comprehensive review of indoor propagation models operating in the 60 GHz band, considering the main scenarios of interest. Propagation mechanisms such as reflection, diffraction, scattering, blockage, and material penetration, as well as large-scale path loss, are discussed in order to obtain a channel model for 60 GHz signals in indoor environments. Finally, comparisons were made using data obtained from a measurement campaign available in the literature in order to emphasize the importance of developing accurate channel models for future wireless communication systems operating in millimeter-waves bands.